Peran Transportasi dalam Perkembangan Peradaban Indonesia Kuno - Ery Soedewo (Balai Arkeologi Sumatera Utara, 2010)
AbstractGood transportation system ensures the smooth flow of people and goods. At the same time, along the transfer of people and goods, it also occured the spread of the ideas from one place to another. Unwittingly, such conditions have ultimately an impact on the growing of a civilization.